(untitled) - Dr. Muhammad Zafar Iqbal , Muhammad Nadil Ali , Dr. Namra Munir (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
This paper aims to identify different resources of learning during the dangerous virus COVID-19 in Pakistan. The basic purposes of this research to identify different instruments which students are used maintain their learning during the deathly virus COVID epidemic.During the COVID 19 Pandemic in PAKISTAN, this research centred on objectively examining the use of information communication technologies to sustain students' learning. Four relevant fields teachers re the subject of the research.Quantitative method of research was selected to conduct the study. The descriptive design was adapted to analysis and collection of the data. Population of the study all the universities teachers re working in the Islamabad. Using the randomly sampling process, the researcher was chosen to sample. By using easy sampling methods, 30 (66.67.percent) male and 15 (33.33 percent) female teachers re chosen sixty- sixty percent replied that they had learned by using of ICTs instruments for their learning and sixty- sixty percent responded to the understanding of ICT techniques and services. There are some hard to understand ICT tools and services, just as seven prospects replied. Seventy- two percent of the students ansteachers red that they had equipment and services for ICTs to handle their everyday activities. The ICTs instrument effected used for maintain students their learning.